2004
DOI: 10.1074/jbc.m403801200
|View full text |Cite
|
Sign up to set email alerts
|

80K-H as a New Ca2+ Sensor Regulating the Activity of the Epithelial Ca2+ Channel Transient Receptor Potential Cation Channel V5 (TRPV5)

Abstract: binding. Electrophysiological studies using 80K-H mutants showed that three domains of 80K-H (the two EFhand structures, the highly acidic glutamic stretch, and the His-Asp-Glu-Leu sequence) are critical determinants for TRPV5 activity. Importantly, inactivation of the EFhand pair reduced the TRPV5-mediated Ca 2؉ current and increased the TRPV5 sensitivity to intracellular Ca 2؉ , accelerating the feedback inhibition of the channel. None of the 80K-H mutants altered the TRPV5 plasma membrane localization nor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 45 publications
(57 reference statements)
1
61
0
Order By: Relevance
“…Inactivation of the EF-hand pair reduced the TRPV5-mediated Ca 2+ current and increased TRPV5 sensitivity to intracellular Ca 2+ , accelerating the feedback inhibition of channel activity. The membrane localization of 80K-H and TRPV5 was not altered, suggesting that 80K-H has a direct effect on TRPV5 activity (Gkika et al 2004). The 80K-H binding-site identified in the C-terminal tail of TRPV5 corresponds to the amino acid sequence MLERK, which is the same region where TRPV5 self-assembly can occur (Table 1; Chang et al 2004).…”
Section: K-hmentioning
confidence: 98%
See 2 more Smart Citations
“…Inactivation of the EF-hand pair reduced the TRPV5-mediated Ca 2+ current and increased TRPV5 sensitivity to intracellular Ca 2+ , accelerating the feedback inhibition of channel activity. The membrane localization of 80K-H and TRPV5 was not altered, suggesting that 80K-H has a direct effect on TRPV5 activity (Gkika et al 2004). The 80K-H binding-site identified in the C-terminal tail of TRPV5 corresponds to the amino acid sequence MLERK, which is the same region where TRPV5 self-assembly can occur (Table 1; Chang et al 2004).…”
Section: K-hmentioning
confidence: 98%
“…Deleting or mutating assembly domains could cause a change in tertiary structure and/or prevent the interaction with auxiliary proteins, thereby affecting channel trafficking and activity. For instance, the assembly domain in the C-terminal tail of TRPV5, the MLERK sequence, is also known to bind the protein 80K-H (Gkika et al 2004). Impaired trafficking observed in the MLERK-mutant of TRPV5 could be explained by the inability to interact with the necessary auxiliary proteins.…”
Section: Ankyrin Repeatsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, identification of the molecular players that associate with TRPV5 and TRPV6 could be pivotal in our understanding of the regulation of these channels. Until now, five regulatory proteins have been identified that associate with TRPV5 and/or TRPV6, i.e., S100A10-annexin 2, calmodulin (CaM), 80K-H, Na ϩ /H ϩ exchanger regulatory factor 2 (NHERF2), and Rab11a (17,22,35,40,46,61,62). S100A10/Annexin 2 S100A10 (also known as p11 or annexin 2 light chain) was identified as an auxiliary protein for TRPV5 and TRPV6 using a yeast two-hybrid system (62).…”
Section: Regulation Of Trpv5 and Trpv6 By Channel-associated Proteinsmentioning
confidence: 99%
“…In this regard, recent studies on other TRP channels indicate that membrane trafficking of TRPs are complex and different Rab-GTPase, dynamin, 80KH, annexins and kinesins might be involved. [74][75][76][77] Based on the structural information available and existing sequence homology among other TRPs, especially with TRPV members and the manner by which the surface expression of TRP channels are regulated, it can be speculated that proteins like Signal Transducing Adaptor Molecule (STAM), Hrs (which downregulate TRPP2 in C. elegans) and Recombinase Gene Activator (RGA, which regulates cell surface expression of TRPV2) may also be involved in the surface expression of TRPV4. [78][79][80] However, further detailed studies are needed to confirm if these proteins really interact and are involved in the surface expression of TRPV4.…”
mentioning
confidence: 99%